Synthesis and investigation of structural, bias-dependent dielectric and impedance behavior of N-GQDs/TiO2 nanocomposites - Kumar, Adesh; Azad, Seema; Chand, Subhash (Indian journal of physics, 2025)
In this study, the TiO2 nanoparticles and N-GQDs were prepared using sol–gel and hydrothermal techniques. The TiO2/N-GQDs nanocomposites were prepared by mechanically milling the powder for four hours continuously in the weight % ratio of 95 TiO2/5 N-GQDs, 90 TiO2/10 N-GQDs, 85 TiO2/15 N-GQDs, and 80 TiO2/20 N-GQDs. We have investigated the structural and impedance behavior of these nanomaterials using XRD, HR-TEM, FTIR, and impedance spectroscopy. The XRD study confirmed the tetragonal structure of TiO2 nanoparticles. The average crystallite size is 12.25 nm for TiO2 which decreases to 11.97 nm for 80 TiO2/20 N-GQDs. The average particle size of N-GQDs is found to be 8.1 nm. Furthermore, we observe that the frequency-dependent dielectric constant of nanocomposites decreases as the concentration of N-GQDs increases up to 20%. However, we find that each sample's dielectric constant increases as the external voltage increases up to 5 V. At 1 kHz, TiO2 NPs depict the dielectric constant as 37.14, which decreases to 8.82 for 80 TiO2/20 N-GQDs NCs at 0 V and from 20.33 to 9.16 at 5 V. Moreover, the increase in bias-dependent dielectric constant and small dielectric loss of up to 0.02 at 10 MHz and 5 V may suggest the use of prepared NCs as a capacitor for electronic devices.